Future competitive bioenergy technologies in the German heat sector: Findings from an economic optimization approach. (15th December 2019) - Jordan, Matthias; Lenz, Volker; Millinger, Markus; Oehmichen, Katja; Thrän, Daniela
Abstract: Meeting the defined greenhouse gas (GHG) reduction targets in Germany is only possible by switching to renewable technologies in the energy sector. A major share of that reduction needs to be covered by the heat sector, which accounts for ∼ 35 % of the energy based emissions in Germany. Biomass is the renewable key player in the heterogeneous heat sector today. Its properties such as weather independency, simple storage and flexible utilisation open up a wide field of applications for biomass. However, in a future heat sector fulfilling GHG reduction targets and energy sectors being increasingly connected: which bioenergy technology concepts are competitive options against other renewable heating systems? In this paper, the cost-optimal allocation of the limited German biomass potential is investigated under long-term scenarios using a mathematical optimization approach. The model results show that bioenergy can be a competitive option in the future. Especially the use of biomass from residues can be highly competitive in hybrid combined heat and power (CHP) pellet combustion plants in the private household sector. However, towards 2050, wood based biomass use in high temperature industry applications is found to be the most cost efficient way to reduce heat based emissions by 95% in 2050. Highlights: Biomass contributes competitively to a future sustainable heat sector. Hybrid CHP pellet combustion plants offer a great GHG reduction potential. In 2050 biomass use is most advantageous in high temperature industry applications. Miscanthus is found to be the most favourable energy crop for heating applications.